The anomalous lithium isotopic signature of Himalayan collisional zone carbonatites in western Sichuan, SW China: Enriched mantle source and petrogenesis. (15th June 2015) - Tian, Shihong; Hou, Zengqian; Su, Aina; Qiu, Lin; Mo, Xuanxue; Hou, Kejun; Zhao, Yue; Hu, Wenjie; Yang, Zhusen
Abstract: Lithium concentrations and isotopic compositions of 38 carbonatites and associated syenites from the Maoniuping, Lizhuang, and Dalucao in western Sichuan, along with previously published and new Pb–Sr–Nd–C–O isotope data and whole-rock analyses, are used to constrain their mantle source and genesis. Carbonatites and syenites are characterized by extremely varying Li concentrations (0.8–120 ppm) and highly variable Li isotopic compositions (−4.5‰ to +10.8‰). Among them, the majority of the carbonatites and syenites have δ 7 Li values between +0.2‰ and +5.8‰, which overlap with the reported values for MORB and OIB; 3 carbonatites have higher δ 7 Li values between +8.7‰ and +10.8‰; 5 carbonatites and 4 syenites have lighter δ 7 Li values between −4.5‰ and −0.3‰. These highly variable δ 7 Li compositions could not have been produced by diffusive-driven isotopic fractionation of Li and thus may record the isotopic signature of the late Proterozoic subcontinental lithospheric mantle (SCLM). This paper demonstrates the existence of anomalous δ 7 Li within the late Proterozoic subcontinental lithospheric mantle, suggesting that the ancient SCLM beneath western Sichuan was modified by interaction with fluids derived from the subducted oceanic crust and marine sediments. The modeling curves of fluids derived from a dehydrated slab (ratios: AOC80 –SED20 to AOC40 –SED60 ) with a representative mantle composition can account for the majority of lithium compositional variations. Some samples with unusual Pb–Sr–Nd–O isotopic compositions and highly variable δ 7 Li compositions are affected by significant involvement of marine sediments in their source region, not contaminated by crustal materials. The carbonatites and syenites in western Sichuan were generated by the partial melting of subcontinental lithospheric mantle, which was metasomatized by the Li-rich fluids derived from the subducted oceanic crust and marine sediments. This melting was most likely triggered by a Cenozoic asthenospheric mantle diapir related to Indian-Asian continental collision and post- or late-collisional stress relaxation in the Oligocene.